Work-related musculoskeletal disorder among midwives, a threat for maternity care - Osman Yimer Mohammed; Kerstin Erlandsson; Tewodros Seyoum; Solomon Hailemeskel; Lemma Derseh; Helena Lindgren (PLoS ONE, 2025)
Background Work-related musculoskeletal disorder is a limiting, painful condition that affects the muscular, skeletal, articular, and nervous tissues of the body. The condition is mainly associated with poor working conditions and awkward body positions. Health professionals, including midwives, are among the most affected workforce globally . The condition affects the health of the professionals and the quality of care that professionals are expected to provide. However, there is a scarcity of information on the magnitude of the condition, its effect on midwifery practice, and associated factors. Objectives: This study aimed to assess the magnitude of work-related musculoskeletal disorder, its effect on midwifery practice, and associated factors among midwives in North Shoa Zone, Amhara Regional State, Ethiopia. Method An institution-based cross-sectional study assessed the magnitude of work-related musculoskeletal disorder (WRMSD), the effect on midwifery practice, and associated factors. The Nordic Musculoskeletal Disorder Scale was used to assess the presence of WRMSDs in the nine regional body parts and its effect. A stepwise backward elimination logistic regression model was used, and significant association was declared at a p-value of less than 0.05. Results A total of 473 (252 (53.3%) female and 221 (46.7%) male) midwives participated in this study. Overall, in the last 12 months, 355 (75.05%, 95% CI: 71.15% − 78.95%) midwives were affected by WRMSD, which was seen in any one of the nine regional body parts. About 45% (162) of them reported being unable to perform their daily tasks while they were affected, and 27% (96) of them sought treatment for their condition. The lower back was the most affected axial body part, reported by 300 (63.4%, 95% CI: 59% − 68%) midwives. Working in awkward or uncomfortable positions was significantly associated with the development of WRMSD (AOR: 1.81, 95% CI: 1.15–2.87). Similarly, awkward positions significantly affected the development of area-specific WRMSD in the lower back, upper back, neck, and limbs. Working in the same position for a longer time, seeing clients daily, and moving heavy objects were among the risk factors associated with developing area-specific WRMSD among midwives. Conclusion The magnitude of work-related musculoskeletal disorders is high among midwives, and a significant number of them were unable to perform their daily tasks. The lower and upper back are the most commonly affected areas. Working in uncomfortable positions and attending to large clients daily were common risk factors. Therefore, training midwives about safe working positions and reducing the workload is commendable.